2015
DOI: 10.1039/c5nj01385b
|View full text |Cite
|
Sign up to set email alerts
|

Efficient mineralization of benzoic and phthalic acids in water by catalytic ozonation using a nickel oxide catalyst

Abstract: Organic acids (OAs) are usually used as refractory model compounds that require prolonged reaction time for their mineralization by different treatments. In this study, benzoic and phthalic acids in aqueous solution were significantly degraded and mineralized by catalytic ozonation in the presence of nickel oxide (NiO). For instance, only 42% mineralization was obtained by direct reaction with molecular ozone, while by catalytic ozonation 98% was achieved. These surprising results led to study in depth the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Diverse publications demonstrated the effect of catalyst in combination with ozone on the intermediate. 17,35,36…”
Section: Ozonation Of Nap In Water With and Without Niomentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse publications demonstrated the effect of catalyst in combination with ozone on the intermediate. 17,35,36…”
Section: Ozonation Of Nap In Water With and Without Niomentioning
confidence: 99%
“…In these works, the authors attributed the effect of NiO at three mechanisms: (1) $OH generation, (2) direct reaction with ozone and (3) complex formation in the surface of NiO. 17 The published results demonstrated that NiO is an effective catalyst for the ozonation process.…”
Section: Introductionmentioning
confidence: 99%
“…The study of BA, PA, and 2,4-D degradation profiles showed an insignificant effect by varying the catalyst concentration (results not shown). This fact is due to that direct reaction with molecular ozone was a feasible method to decompose model compounds achieving up to 95% removal of three compounds in 20 min [20,30]. Oxalic acid (OA) is the main recalcitrant product formed from the model compounds elimination and it was chosen to study the catalyst dose influence.…”
Section: Influence Of Catalyst Dosage On Organic Compounds Eliminationmentioning
confidence: 99%
“…OH), which can accelerate the kinetics of mineralization of refractory organic pollutants in wider range of pH . Recently, micro‐ and nano‐dimensional transition and non‐transition metal oxides have been widely studied as catalysts for ozonation reaction for the degradation of various organic pollutants (as shown in Table S1) ; but many of those catalysts was evident to be effective only at low and near to neutral pH. On the contrary, pH of the dye effluent of most of the textile industries roughly varies in the range of neutral to alkaline …”
Section: Introductionmentioning
confidence: 99%